SPE Reservoir Simulation Symposium 2003
DOI: 10.2118/79700-ms
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Geomechanical and Reservoir Modeling on Parallel Computers

Abstract: In coupled geomechanics and reservoir modeling, the finite element discretization of the force balance equation leads to very large linear systems, whose solution is both time and memory consuming. ICCG (Incomplete Cholesky Factorized Conjugate Gradient) is a popular technique for solving for displacements, but the technique is limited to about 60,000 nodal points on desktop machines. Most large 3D field scale problems will have to be run on parallel machines. In this paper, we present a reduced-communication,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 18 publications
0
55
0
1
Order By: Relevance
“…Parallel processing with high performance computing clusters can alleviate these challenges to a good extent. Wang et al (1997), Zhang et al (2001), Dogru et al (2002), Gai et al (2003), andDeBaun et al (2005) demonstrated the necessity, advantages, and applicability of using parallel processing for large-scale reservoir simulations.…”
Section: Parallel Processingmentioning
confidence: 99%
“…Parallel processing with high performance computing clusters can alleviate these challenges to a good extent. Wang et al (1997), Zhang et al (2001), Dogru et al (2002), Gai et al (2003), andDeBaun et al (2005) demonstrated the necessity, advantages, and applicability of using parallel processing for large-scale reservoir simulations.…”
Section: Parallel Processingmentioning
confidence: 99%
“…In both levels, i.e. reservoir and near borehole, the flow simulation needs to be coupled to geomechanics in order to predict these changes and their impact [40,69,74], which causes a significant increase in CPU time and memory requirements.…”
Section: Motivationmentioning
confidence: 99%
“…He also implemented a model that includes thermal effects and a plasticity model for the porous medium. Also at CSM, Gai [74] used continuous elements for displacements and a cell-centered finite difference method for pressure and implemented an iteratively coupled scheme to find the numerical solution. She also tackled the multiphase flow version of the poroelasticity equations.…”
Section: Literature Review 121 Geomechanicsmentioning
confidence: 99%
“…The mathematical formulation considers a bounded domain Ω ⊂ R n ,n ÂŒ 2, 3 and its boundary is Γ ÂŒ ∂Ω, and a time interval of interest 0, â„‘Âœ.LetT h be a non-degenerate, quasi-uniform conforming partition of Ω composed of triangles or quadrilaterals for two-dimensional problems, and hexahedra or tetrahedra for three-dimensional problems. For instance, Gai [5] thesis showed that deformable porous media, i.e., the reservoir matrix, the single-phase flow model equation derives from the continuity equation, i.e., a mass balance statement, for slightly incompressible single-phase flow and Darcy's law which yields:…”
Section: Mathematical Model For Thermo-poroelasticitymentioning
confidence: 99%